OPTIMASI ENZIM ?-AMILASE DARI BACILLUS AMYLOLIQUEFACIENS O1 YANG DIINDUKSI SUBSTRAT DEDAK PADI DAN KARBOKSIMETILSELULOSA - Soeka, Yati Sudaryati; Rahmansyah, Maman; ., Sulistiani (JURNAL BIOLOGI INDONESIA, 2015)
ABSTRACTBacterial code O1 had been isolated from the leaven of fermented cassava. Based on molecular analysis by partial sequences of 16S rDNA and the phylogenetic character interpretation with Neighbor Joining Method, the strain was identified as Bacillus amyloliquefaciens O1. Bacterial enzymatic activity of ?-amylase was clarified due to the affect of temperature and pH, and as well as its enzymatic stability to convert 2% soluble starch in 100 ml standard media. Aim of the study was to provide benefit in regard on ?-amylase application as crude enzyme extract from the bacteria. In this study, the bacterial strain was being activated to produce ?-amylase by modifying substrates containing cassava starch, rice bran (RB), and carboxymethylcellulose (CMC) in five times volumes (500 mL) of the first scale setting in the standard media.  The result, reducing sugar as a result of enzymatic activity process increased 40 and 55 times in the modified media containing RB and CMC, respectively after 24 hours incubation. In the next 24 hours observation, enzyme activity in bacterial culture based on the RB media was able to degrade amylum in the muslin material containing amylum which was plunged in the media, 1.23 times higher compared to bacterial culture based on the CMC media. Media formula used in the study was able to induce extracellular enzyme activity as well as bacterial culture growth. Keywords: ?-amylase, Bacillus amiloliquefaciens, rice bran, carboxymethylcellulose